GIS and Remote Sensing Techniques for Measuring Agriculture Land Loss in Balik Pulau Region of Penang State, Malaysia - Mohammed , Khalid Sabbar; Elhadary, Yasin; Samat , Narimah; Omar, Najat Qader (Asian Journal of Agriculture and Rural Development, 2015)
Currently, Malaysia like other Asian countries has experienced rapid expansion of urbanization due to economic development, industrialization, massive migrations as well as natural population growth. This expansion particularly unplanned consumed a huge amount of arable land in the urban milieu and in its surrounding areas. This paper aims to measure arable land loss due to massive urbanization in Balik Pulau region of Penang State, Malaysia. Landsat TM (Thematic Mapper) images of 1992 and 2002 at the resolution of 30 m and Landsat ETM (Enhanced Thematic Mapper) 2010 have been used to measure the rate of urban expansion and its impact on agricultural land. The integration of Remote Sensing and Geographical information system GIS were used to quantify the conversion of arable land to built-up areas in Penang State. The result reveals that built-up areas have expanded rapidly during the last four decades at the expense of agricultural land in Balik Pulau Region. Built-up areas had increased from 1793.22 ha in 1992 to 3235.38 ha in 2002, while agricultural areas decreased from 6171.32 to 4727.83 ha during the same period. The expansion of Built-up area is directed towards low-lying areas with less topographical barrier causing heavy loss in productive land and environmental degradation. In order to safeguard the environment and maintain arable land, urbanization should be controlled and rationalized through legislative measures, wise policy and public awareness. More attention should be given to the areas that have witnessed massive urbanization and coordination between various sectors involved in development is a must.